Migrant Laborers in China and Their Contributions to Rural Development - Guzman, Charles Joseph G. De (Cultural and religious studies, 2017)
This paper will look at the importance that the migrant labors in China are doing today. The main question posed in this paper is "how migrant labors in China are contributing to rural development?". Furthermore, the paper will answer the following sub-questions: (1) Is migration an important factor in the development of rural areas? (2) Can migration bridge the poverty gap between urban and rural areas? The objectives of this paper are the following: (1) to identify the migrant labors contributions in China’s rural development; (2) to look into the importance of migration for the rural Chinese; and (3) to know and analyze the problems that migrant workers in China are facing in relation to their migratory work. Furthermore, this paper posits that migrant labors in China are contributing to rural development through their remittances, their investments, and the new knowledge and techniques that they acquired in the urban areas which they share in their home areas. In addition to that, this research looks at the migrant labors’ remittances, their investments, and the new knowledge and techniques that they acquired in their home areas as their contributions to rural development.